Metal-organic frameworks-based hydrogen storage strategies and applications. Issue 1 (1st December 2022) - Li, Alex
Abstract: Against the backdrop of rising emissions of greenhouse gasses and the need for sustainable fuel, hydrogen storage has recently become a popular energy storage option due to its many benefits, such as high energy capacity, low concentrations of side products, and relative ease of access. However, hydrogen storage is not perfect and possesses some critical flaws that prevent it from reaching its full potential, which include volatility and flammability. There are many candidates for hydrogen storage and also extant technologies to target hydrogen storage. Among all the ways proposed to store hydrogen, metal-organic frameworks (MOFs) have become increasingly popular because of their exemplary high surface area and adaptable pore structure. This research explores the various developments of MOFs in the field of hydrogen storage and how they may be improved and compared to one another. It will discuss the issues with current MOFs and design procedures and elements, such as making use of void spaces in MOFs. Then it will proceed to explore how MOFs have been enhanced through impregnation, catenation, and open metal sites. Lastly, this review will feature some breakthrough MOFs that have been promising for hydrogen storage.